W poszukiwaniu sojuszników. Polskie próby zbliżenia z państwami Europy Środkowej i Północnej (1921−1939) - Furdyna, Marcin (Sprawy Międzynarodowe, 2018)
Located between Germany and the Soviet Union in the interwar period, Poland concluded defensive alliances with France and Romania in 1921. Simultaneously, Warsaw tried to create room for cooperation with other, smaller states in central and northern Europe. In the ﬁrst case, close cooperation with the so-called Little Entente, formed by Czechoslovakia, Romania and Yugoslavia, was successfully blocked by Prague, which regarded its interests as different from the Polish ones. Rapprochement between Poland, the Baltic States and Finland, though initiated in the early 1920s, was doomed to failure because of the disagreement between Poland and Lithuania over the Vilnius region. Furthermore, Józef Beck’s idea of creating a bloc of neutral states situated between Germany and the Soviet Union was turned down by the Scandinavians, who wanted to avoid a possible war.